A A Comparison of the Optical Method with the Mechanical Method in Routine Coagulation Tests: A Comparison of the Optical Method - Ulfer, Gozde (Journal of Medical Biochemistry, 2025)
Background:This study aimed to compare the prothrombin time (PT), international normalized ratio (INR), and activated partial thromboplastin time (aPTT) values obtained using the photo-optical method and to assess these values according to the reference method which was the mechanical method .Methods:Plasma samples from 340 patients, submitted to our hospital’s biochemistry laboratory for PT, INR, and aPTT analyses, were assayed using the mechanical coagulometric measurement method in a Stago Compact Max3 automated coagulation analyzer, which served as the reference device. The same samples were also analyzed using the Sunbio UP5500 automated analyzer with a simultaneous optical method. Turbid samples were analyzed in both devices without exclusion from the study. Correlation coefficient analysis was carried out using SPSS to assess intervariable correlations, and Passing-Bablok regression analysis was performed in R software version 3.6.0 for the comparison of PT, INR, and aPTT values between the two devices. Bland-Altman plots were used to analyze agreement.Results:A good level of statistically significant agreement was found between the PT and INR values measured by the Stago Compact Max3 and Sunbio UP 5500 devices (intraclass coefficient [ICC]: 0.627, p=0.001; p
Keywords: Coagulation Tests; Optic Method; Mechanic Method; Bland-Altman plots; Passing-Bablok regression